Implementasi Good Corporate Governance Terhadap Nilai Perusahaan Melalui Pengungkapan Corporate Social Responsibility - Sura Klaudia; Parawiyati Parawiyati; Harmono Harmono (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2022)
This study aims to examine the effect of good corporate governance through disclosure of corporate social responsibility on stock prices that focuses on BUMN (Badan Usaha Milik Negara) because BUMN (Badan Usaha Milik Negara) is a government-owned company that has rules in law to implement good corporate governance and implementing corporate social responsibility, so this research includes government board proxies in the elements of good corporate governance. This research is a quantitative study using secondary data. Sampling in this study using purposive sampling technique with the companies that became the sample of the study amounted to 11 BUMN (Badan Usaha Milik Negara) during the 2015-2018 observation year. The results showed that the independent board of commissioners had no effect on firm value, the independent board of commissioners in BUMN (Badan Usaha Milik Negara) had no effect on stock prices through disclosure of corporate social responsibility, while other tests showed a positive effect of government ownership, managerial ownership The audit committee through disclosure of Corporate Social Responsibility on share prices